Ba2B7O12F with novel FBB [B7O16F] and deep-ultraviolet cut-off edge. Issue 2 (13th November 2020) - Miao, Zhaohong; Yang, Yun; Wei, Zhonglei; Yang, Zhihua; Pan, Shilie
Abstract : A new fluorooxoborate Ba2 B7 O12 F features novel FBB [B7 O16 F] and two different sizes of channels in its anionic structure, which possesses a deep-ultraviolet cutoff edge of 180 nm and a large bandgap of 6.67 eV. Abstract : A new member in the barium fluorooxoborate family, namely Ba2 B7 O12 F, was obtained by the high-temperature solution method in an open system under ambient pressure. The structure features a new fundamental building block [B7 O16 F], which interconnects with each other to form the anionic framework [B7 O12 F]∞ with two different caves in which the cations reside. The experiment result indicates that Ba2 B7 O12 F possesses a deep-ultraviolet cut-off edge below 180 nm.